Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan Melalui Motivasi Sebagai Variabel Intervening Pada Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Sumatera Barat - M Fikri Pratama; Marta Widian Sari; Muhammad Pondrinal (Jurnal Ekonomi dan Bisnis Digital, 2026)
The purpose of this study is to identify and examine the effect of Leadership and Work Discipline on Employee Performance through Motivation as an intervening variable at the Regional Financial and Asset Management Agency of West Sumatra Province. The data analysis method used a questionnaire, with a sample of 45 respondents. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. Based on the results of this study, it can be concluded that: (1) Leadership has a positive and significant effect on Motivation at the Regional Financial and Asset Management Agency of West Sumatra Province; (2) Work Discipline has a positive and significant effect on Motivation at the Regional Financial and Asset Management Agency of West Sumatra Province; (3) Leadership does not have a positive and significant effect on Employee Performance at the Regional Financial and Asset Management Agency of West Sumatra Province; (4) Work Discipline does not have a positive and significant effect on Employee Performance at the Regional Financial and Asset Management Agency of West Sumatra Province; (5) Motivation does not have a positive and significant effect on Employee Performance at the Regional Financial and Asset Management Agency of West Sumatra Province; (6) Motivation does not mediate the effect of Leadership on Employee Performance at the Regional Financial and Asset Management Agency of West Sumatra Province; and (7) Motivation does not mediate the effect of Work Discipline on Employee Performance at the Regional Financial and Asset Management Agency of West Sumatera Province